Hour-glass deformity of the pulmonary valve: a third type of pulmonary valve stenosis. Issue 2 (August 1988) - Milo, S; Fiegel, A; Shem-Tov, A; Neufeld, H N; Goor, D A
Abstract : In the 12 years from 1975 to 1987, 55 patients had open pulmonary valve surgery for isolated congenital stenosis of the pulmonary valve. Three types of pulmonary stenosis were seen: (a) dome-shaped pulmonary stenosis (34 patients); (b) dysplastic pulmonary valves with thick cauliflower-like cusps (12 patients), and (c) hour-glass deformity of the pulmonary valve, with "bottle-shaped" sinuses (nine patients). This third type has not been described before. Preoperative identification of the valve structure is important because the choice of treatment (balloon dilatation for some dome-shaped valves and excision for dysplastic and hour-glass valves) depends on the type of stenosis.